Nepal Country Assistance Evaluation, 2003–08 - World Bank (Washington, DC, 2012)
The FY03-08 evaluation period was one of tumultuous political turmoil, conflict, and dramatic change in Nepal; today, prospects for sustainable peace are brighter, though still fragile. In such difficult and unpredictable conditions, formulating and implementing an effective development assistance strategy and programs were great challenges for development partners, including the Bank. To its credit, the Bank managed to remain constructively engaged in Nepal despite a challenging political and security context and has achieved some significant results on the ground. Nevertheless, the Bank's strategy was poorly adapted to the country's conflict situation and political instability, and until recently (FY08) underwent little adjustment in response to the rapidly-evolving conditions on the ground. Looking forward, Independent Evaluation Group (IEG) recommends that International Development Association (IDA) introduce greater realism into its strategy and program design and keep these flexible against a backdrop of a clear long-term vision, applying frequent course corrections in response to changing circumstances and consulting widely with national stakeholders and development partners. Other than through its existing portfolio of two hydropower projects, International Finance Corporation (IFC) did not make a significant contribution to Nepal's development over most of the review period. IFC's gradual re-engagement beginning in 2006 was successful, resulting in two Global Trade Finance Program (GTFP) investments, an investment in a domestic airline in 2008, a pipeline of investment projects in the financial sector, and a constructive dialogue with the government on the business climate.